Bombay 1937 : la fascination d’une métropole pour le goût moderne - Éléonore Muhidine (In Situ)
Bombay, in 1937, was a building site of a city. It was attentive to international trends and witnessing profound political upheavals. In the forms of modern architecture, local builders and independentist architects saw a means of breaking with the colonial neogothic city whilst contributing, at the same time, to the reinforcement of the national economy. Cinemas, banks, insurance company office blocks, parsi temples and apartment buildings rapidly adopted the new decorative style with its geometrical forms and monumental accents. The Bombay of the 1930s was also a cosmopolitan metropolis, a place of refuge for European artists and travellers, for whom the modernising India of the interwar period could help satisfy their ambitions. In its plurality, the ‘Art Dekho’ of Bombay is a reflection of the synthesis of western influences reaching the city through its maritime commerce. But what subsequently becomes the ‘Indo Deco’ style is also a reinterpretation of vegetally inspired ornamentation, already present in the royal palaces of Rajasthan and the villas of the wealthy during the years from 1910 to 1920. Based on research in the Indian archives and on several photographic surveys carried out in Mumbai (as the city is called today) in 2022 and 2023, this article offers an inventory of the architectural tendencies claiming to represent the modern decorative style in the Bombay of the 1930s and 1940s. After 1947, this collective experimentation gave rise to an alternative form of modernity, influenced by decorative reminiscences borrowed from Indian cultural symbolism. This modernity was to find expression in the anonymous constructions of the suburbs up until the 1960s.